USE OF RETROTRANSPOSON MARKERS FOR ANALYSING THE GENETIC DIVERSITY OF WILD EMMER WHEAT (TRITICUM DICOCCOIDES) - Tagimanova , D.S.; Novakovskaya , A.P.; Uvashov , A.O.; Khapilina , O.N.; Kalendar , R.N. (Eurasian Journal of Applied Biotechnology, 2015)
The wild ancestor of all cultivated tetra- and hexaploid wheat, wild emmer wheat (Triticum dicoccoides), harbours considerable genetic diversity. This diversity might be expected to display eco-geographical patterns of variation, conflating gene flow, and local adaptation. Similarly, retrotransposons, as self-replicating entities comprising the bulk of genomic DNA in wheat, are expected to generate generally neutral variation due to their transpositional activity. Here, we examined the genetic diversity of 14 Israeli and one Turkish population of wild emmer wheat, based on the retrotransposon marker methods IRAP (Inter-Retrotransposon Amplified Polymorphism) and REMAP (Retrotransposon-Microsatellite Amplified Polymorphism). The level of genetic diversity we detected was in agreement with previous studies that have used a variety of marker systems to assay genes and other genomic components. The genetic distances failed to correlate with the geographical distances, suggesting local selection on geographically widespread haplotypes (“weak selection”). However, the proportion of polymorphic loci correlated with the latitude of the population and the genetic diversity correlated with the longitude. Principal component analysis of the marker data resulted in separation of some of the populations.